(untitled) (Journal of Surgical Sciences, 2019)
Colorectal cancer, a rising health concern of both east and west , can be prevented and it’s mortality can be reduced by screening all men and women of average risk at the age of 50 years or older and at an earlier age for high risk group of colorectal cancer. Several tests are available for colon cancer screening, including fecal occult blood test (FOBT), flexible sigmoidoscopy, double-contrast barium enema, and colonoscopy. Direct and indirect evidence indicates that all the tests are effective, but they differ in their sensitivity, specificity, cost, and safety. The available evidence does not currently support choosing one test over another. In addition, other new colorectal cancer tests, such as virtual colonoscopy or stool-based molecular testing, have the potential to become important screening tests in the future. Journal of Surgical Sciences (2015) Vol. 19 (2) : 61-66